(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
This thesis analyzes the sociological aspects of information consumption in modern society, the communicative behavior of the digital generation, and the social consequences of disinformation. The study examines the concept of the “digital generation” from a sociological perspective, highlighting the process of forming information consumption culture among youth. The article explores the phenomena of disinformation, fake news, and information manipulation emerging in the global media environment, analyzing them in relation to the social transformations observed in Uzbekistan. It also investigates the criteria of trust in information sources, behavioral factors in selecting information flows, and the distinctive features of social consciousness developing in digital networks. The research results substantiate the need for sociological analysis of digital communication processes, as well as the importance of enhancing media literacy and building social immunity against disinformation. The thesis also provides scientific and practical recommendations for improving digital culture and information policy in the context of Uzbekistan.